EVALUATION OF RESISTANCE TO POTATO VIRUS Y OF CULTIVARS IN PRE-REGISTRATION (STATUTORY) TRIALS - Michalak, Krystyna; Chrzanowska, Mirosława (Plant Breeding and Seed Science, 2017)
The paper describes testing potato cultivars for resistance to potato viruses in field and greenhouse condi-tions according to the scheme of the statutory trials. Seed tubers of tested cultivar are planted in the field in two replications with 30 tubers each. On both sides of each cultivar, 15 PVY-infected tubers, i.e. the source for PVY inoculation, are planted. The evaluation includes standard cultivars of known resistance levels to PVY. The progeny tubers are collected in autumn and growing-on testing is carried out in greenhouse condi-tions to estimate the number of plants infected with PVY. The other method is to evaluate the resistance of potato cultivars in greenhouse conditions. At present, the resistance of cultivars is evaluated only with respect to PVY, the most important potato virus. Two strains are used in the evaluation, i.e. PVYN-Wi and PVYNTN. For each testing cultivar, 10 plants are mechanically inoculated with each PVY strain. The analysis of the results makes it possible to classify the cultivars into four resistance groups on a 1-9 scale: highly resistant (with the resistance score of 8), resistant (with a value of 7), mid-resistant (with a value 5-6), and susceptible (with a value of 3-4). The ”9” rating is specified after the registration of the cultivars based on molecular tests, that validate the presence of a marker linked to extreme resistance (ER) gene Rysto.